2012
DOI: 10.1111/j.1365-2753.2010.01525.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical specialization and training – its relation to clinical outcome for colorectal cancer surgery

Abstract: The outcomes in colorectal surgery continue to steadily improve. The training of specialized colorectal surgeons is a major contributing factor towards this improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 52 publications
2
6
0
1
Order By: Relevance
“…Several studies indicate that the surgical outcome is improved by careful planning and if performed by highskilled surgeons [35][36][37]. Our morbidity rate is similar to other published figures [4][5][6], and we have a mortality rate within the range published [1,3,4,6,38], indicating that the surgery performed was of high quality.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies indicate that the surgical outcome is improved by careful planning and if performed by highskilled surgeons [35][36][37]. Our morbidity rate is similar to other published figures [4][5][6], and we have a mortality rate within the range published [1,3,4,6,38], indicating that the surgery performed was of high quality.…”
Section: Discussionsupporting
confidence: 89%
“…A population study carried out in Great Britain showed that mortality rate after a resection of oesophageal, gastric and pancreatic cancers was indirectly proportional to the number of cases previously operated on by the surgeon [2]. Similar observations concern the risk of post-operative complications in patients operated on for colorectal cancer [3], yet it is the individual experience of the surgeon and the entire surgical team is built not only from the number of the surgeries performed, but it comes also from a critical analysis of the results and the rate of the complications, perioperative mortality, the length of hospital stay etc. Therefore, it is not a surprise that an increasing number of data supports the argument that every surgeon should have the chance to critically monitor the results of the treatment they have conducted [4].…”
Section: Final Remarkssupporting
confidence: 48%
“…This high rate of prevalence of colorectal cancer among young people is attributed to the age structure of the young in these countries and the rate of prevalence among the elderly compared to Western countries (Ansari et al, 2007). The reported 5-Year survival in Europe is 56% for men and 60% for women (Angell-Andersen et al, 2004;Omejc et al, 2004) [In their study conducted in England, Anwar et al, (2012) reported 5-year survival rate to be 50%. Farzianpour et al, (2013) indicated that the general quality of life among patients with cancer is low in Iran.…”
Section: Introductionmentioning
confidence: 99%